A case report of Adult-onset Still's disease presenting with acute fibrinous and organising pneumonia. Issue 4 (March 2020) - Perry, Robert; Christidis, Dimitrios; Nicholson, Andrew G; Schomberg, Lucy; Cheent, Kuldeep
Adult-onset Still's disease is a rare inflammatory disorder characterised by fever, arthritis and rash. It can present in a number of ways and is associated in 5% of cases with parenchymal lung involvement. We present the case of a 37-year-old man who initially presented with fever, weight loss and pancytopaenia. He gradually deteriorated requiring non-invasive ventilation with a Computerised tomography of his chest showing bilateral nodular infiltrates. An open lung biopsy showed acute fibrinous organising pneumonia, which responded well to corticosteroid treatment. He then re-presented over three years later with a similar systemic illness although with less severe lung involvement. Following extensive further investigations, he was diagnosed with Adult-onset Still's disease fulfilling the Yamaguchi criteria. We feel this case is important due to the rare association of Adult-onset Still's disease and interstitial lung disease. More specifically, we are not aware of any published cases of Adult-onset Still's disease with acute fibrinous organising pneumonia.